O relacionamento entre pais e filhos fundamentado em princípios cristãos - Silva, Ilton Antonio da (2013)
The research is bibliographic; it investigates the Holy Scriptures, secular literature and seeks to leave a guideline with a psychological and Christian foundation about the relationship of parents and children in the initial years of the human being. It highlights the importance of the human development and the value of knowledge of this formative process, since this cooperates with the appropriate formation of the child. It describes the necessary responsibility beginning with the intrauterine existence, since the life of the human being begins at the moment that the originating germinal cells of the parents meet. It deals with the development of the personality which develops beginning with the birth and the importance of the adequate posturing of the parents anchored in the good witness. It highlights that the knowledge of the factors which permeate the existence of the child will help in the formation of the children within affectionate and effective relations. It mentions biblical principles and concepts which guide the relation in the formative years of the child, pointing out the home as an institution of high relevance in the constitution of the human being. It says that in the Christian context, the faith begins in the home, where the instruction and witness of the parents implant the divine precepts in the children so that God is present in the daily experiences. It emphasizes love as the integrating path for the construction of healthy and effective relationships, highlighting it as the uncommon conjuncture in which life fulfills its designs, being the base of solid relations, especially the dimension of unconditional love. It means that asking forgiveness and forgiving are fundamental attitudes which nourish the interaction. It explains discipline in the contexture of teaching the child the appropriate path, however it warns that the child will only respond positively if it feels truly loved and accepted. It specifies that within these characteristics the love will be adequate and will work as an integrating effective path in the relationship with the children.